KARAKTERISTIK PRODUK HUKUM DALAM KONFIGURASI POLITIK (Analisis terhadap Undang-Undang Nomor 41 Tahun 2004 tentang Wakaf) - Rahmah, Nur (Jurnal GeoCivic, 2024)
The political situationÂ of a nation (political configuration) very dominantly intervenes in the character of the legal product that is formed, meaning that the two work in harmony. Theoretically, the dichotomous democratic political configuration gives rise to responsive/autonomous legal products. Likewise, the character of conservative/orthodox law emerges from an authoritarian (non-democratic) political configuration. The government's renewal of the Waqf Law in the early reform era is an example of a new legal product that emerged from the political configuration of that time. The renewal of this law is a manifestation of the responsive character of law.